A systematic review of the clinical utility of the concept of self‐disgust. (18th November 2018) - Clarke, Aoife; Simpson, Jane; Varese, Filippo
Abstract : This systematic literature review examined the clinical utility of the construct of self‐disgust in understanding mental distress. Specifically, the review assessed whether there is a shared conceptual definition of self‐disgust, the face and construct validity of the quantitative assessment measures of self‐disgust, and the predictive validity of self‐disgust in formulating the development of a range of psychological difficulties. A systematic database search supplemented by manual searches of references and citations identified 31 relevant papers (27 quantitative, 3 qualitative, and 1 mixed). Analysis of qualitative papers indicated a number of shared features in the definition of self‐disgust, including a visceral sense of self‐elicited nausea accompanied by social withdrawal and attempts at cleansing or suppressing aspects of the self. Quantitative assessment measures appeared to capture these dimensions and evidenced good psychometric properties, although some measures may have only partially captured the full self‐disgust construct. Strong relationships were observed between self‐disgust and a range of mental health presentations, in particular, depression, body‐image difficulties, and trauma‐related difficulties. However, these relationships are smaller when the effects of other negative self‐referential emotions were controlled, and stronger conclusions about the predictive validity of self‐disgust are limited by the cross‐sectional nature of many of the studies.